2013
DOI: 10.1007/s10754-013-9136-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nursing home ownership on hospitalization of long-stay residents: an instrumental variables approach

Abstract: Hospitalizations among nursing home residents are frequent, expensive, and often associated with further deterioration of resident condition. The literature indicates that a substantial fraction of admissions is potentially preventable and that nonprofit nursing homes are less likely to hospitalize their residents. However, the correlation between ownership and hospitalization might reflect unobserved resident differences rather than a causal relationship. Using national minimum data set assessments linked wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 45 publications
(52 reference statements)
0
39
0
1
Order By: Relevance
“…In addition, absolute or relative distance has been used as an instrumental variable (IV) in analyses of other outcomes. Distance strongly predicts choice of provider in various clinical contexts (McClellan, McNeil, and Newhouse 1994;Zwanziger, Mukamel, and Indridason 2002;Hirth et al 2003Hirth et al , 2014Brooks et al 2006;Shugarman and Brown 2006;Grabowski et al 2013). In the dialysis context, Brooks et al (2006) found the relative proximity to for-profit and nonprofit dialysis facilities to be the strongest predictor of the type of facility chosen, and that use of this measure as an IV eliminated the relationship between ownership and patient survival that existed in observational data.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, absolute or relative distance has been used as an instrumental variable (IV) in analyses of other outcomes. Distance strongly predicts choice of provider in various clinical contexts (McClellan, McNeil, and Newhouse 1994;Zwanziger, Mukamel, and Indridason 2002;Hirth et al 2003Hirth et al , 2014Brooks et al 2006;Shugarman and Brown 2006;Grabowski et al 2013). In the dialysis context, Brooks et al (2006) found the relative proximity to for-profit and nonprofit dialysis facilities to be the strongest predictor of the type of facility chosen, and that use of this measure as an IV eliminated the relationship between ownership and patient survival that existed in observational data.…”
Section: Discussionmentioning
confidence: 99%
“…; Hirth et al. ). The counterfactual provider for patients in the PT Later and No PT groups was the closest PT within their insurance plan group ID, which is a proxy for providers “in network.” The counterfactual provider for patients in the PT First group was any provider (excluding hospitals) closest to the patient within their insurance plan group ID.…”
Section: Methodsmentioning
confidence: 98%
“…; Hirth et al. ), hospital affiliation (Rahman, Zinn, and Mor ), and the availability of physician extender and nurse staffing ratios (Harrington et al. ; Schnelle et al.…”
Section: Methodsmentioning
confidence: 99%